2015
DOI: 10.1155/2015/701480
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin Levels in Gram-Positive, Gram-Negative, and Fungal Bloodstream Infections

Abstract: Procalcitonin (PCT) can discriminate bacterial from viral systemic infections and true bacteremia from contaminated blood cultures. The aim of this study was to evaluate PCT diagnostic accuracy in discriminating Gram-positive, Gram-negative, and fungal bloodstream infections. A total of 1,949 samples from patients with suspected bloodstream infections were included in the study. Median PCT value in Gram-negative (13.8 ng/mL, interquartile range (IQR) 3.4–44.1) bacteremias was significantly higher than in Gram-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
89
3
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(122 citation statements)
references
References 33 publications
16
89
3
7
Order By: Relevance
“…The diagnostic accuracy of PCT for this differentiation was determined by ROC analysis, revealing an optimal cutoff value of 3.11 ng/mL, resulting in 93.3% specificity and 63.9% sensitivity [16]. In a similar study, Leli et al [18] found that an optimal PCT cutoff value of 1.6 ng/mL could be used to distinguish GN infections from fungal infections with 96% specificity and 77% sensitivity. Martini et al [19] also demonstrated that an optimal PCT cutoff value of 2 ng/mL could be used to distinguish Candida sepsis from bacterial sepsis with 92% sensitivity and 93% specificity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The diagnostic accuracy of PCT for this differentiation was determined by ROC analysis, revealing an optimal cutoff value of 3.11 ng/mL, resulting in 93.3% specificity and 63.9% sensitivity [16]. In a similar study, Leli et al [18] found that an optimal PCT cutoff value of 1.6 ng/mL could be used to distinguish GN infections from fungal infections with 96% specificity and 77% sensitivity. Martini et al [19] also demonstrated that an optimal PCT cutoff value of 2 ng/mL could be used to distinguish Candida sepsis from bacterial sepsis with 92% sensitivity and 93% specificity.…”
Section: Discussionmentioning
confidence: 99%
“…According to several studies, low concentrations of PCT in critically ill patients might suggest fungal infection. Thus, PCT levels could be used specifically and sensitively to distinguish GN sepsis from fungal sepsis [15,16,17]. The diagnostic accuracy of PCT for this differentiation was determined by ROC analysis, revealing an optimal cutoff value of 3.11 ng/mL, resulting in 93.3% specificity and 63.9% sensitivity [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a critically ill patient with clinical sepsis, Gram-negative bacteraemia seems to be associated with higher PCT levels than Gram-positive bacteraemia [14]. Although the mechanism underlying different PCT production in response to different bacterial pathogens is not completely clear, it could possibly be explained by the different interactions of Grampositive or Gram-negative bacteria with host's cells and different pathogen-associated molecular patterns [41]. E. coli bacteraemia/sepsis usually triggers an extremely high, S. aureus bacteraemia/sepsis only a moderate rise of PCT levels.…”
Section: Discussionmentioning
confidence: 99%
“…Additional results showed a significant difference in median PCT values between Enterobacteriaceae and nonfermentative G-bacteria. 4 An early diagnosis of bacteraemia is crucial to facilitate adequate treatment of severe infections. A PCT level > 2 ng/mL was reported in 71% cases in G-bacteraemia patients, whereas in patients with G+ bacteraemia this level of PCT was reported only in 33%.…”
mentioning
confidence: 99%